Epidemiology of the injuries sustained by elite spanish under-18 and under-20 rugby players - Mencia, C. S.; Ramos-Álvarez, J. J.; Veliz, R. R.; Murias-Lozano, R.; Aramberri, M.; Saló, J. C. (International Journal of Sports Medicine, 2023)
This study examines the injuries suffered by players (n=166) of the Spanish national men`s under-18 and under-20 rugby teams between 2015 and 2017, and identifies the actions involved in their occurrence. All injuries (total n=78) sustained during matches and training were recorded as recommended by World Rugby, and injury incidence rates per 1000 player-hours (ph) calculated for both types of activity. Injuries occurred more commonly during matches than during training (incidence 105.3 [95% CI: 78.7-131.9] per 1000 [ph] of match play, vs 1.16 [95% CI: 0.69-1.62] per 1000 ph of training), and most days absent per 1000 ph during matches with<3 days rest since the previous match (4209.2 [95% CI: 3516.2-4902.1] per 1000 ph of match play, vs 1947.4 [95% CI: 1511.8-2382.9] per 1000 ph of match play in matches with>3 days rest). These results provide information that may be useful in the development of strategies aimed at reducing the incidence of injuries.